In vitro evaluation of the cyto-genotoxic potential of Ruthenium(II) SCAR complexes: A promising class of antituberculosis agents - De Grandis, Rone Aparecido [UNESP]; Resende, Flávia Aparecida; da Silva, Monize Martins; Pavan, Fernando Rogério [UNESP]; Batista, Alzir Azevedo; Varanda, Eliana Aparecida [UNESP] (Elsevier, 2016)
Tuberculosis is a top infectious disease killer worldwide, caused by the bacteria Mycobacterium tuberculosis. Increasing incidences of multiple drug-resistance (MDR) strains are emerging as one of the major public health threats. However, the drugs in use are still incapable of controlling the appalling upsurge of MDR. In recent years a marked number of research groups have devoted their attention toward the development of specific and cost-effective antimicrobial agents against targeted MDR-Tuberculosis. In previous studies, ruthenium(II) complexes (SCAR) have shown a promising activity against MDR-Tuberculosis although few studies have indeed considered ruthenium toxicity. Therefore, within the preclinical requirements, we have sought to determine the cyto-genotoxicity of three SCAR complexes in this present study. The treatment with the SCARs induced a concentration-dependent decrease in cell viability in CHO-K1 and HepG2 cells. Based on the clonogenic survival, SCAR 5 was found to be more cytotoxic while SCAR 6 exhibited selectivity action on tumor cells. Although SCAR 4 and 5 did not indicate any mutagenic activity as evidenced by the Ames and Cytokinesis block micronucleus cytome assays, the complex SCAR 6 was found to engender a frameshift mutation detected by Salmonella typhimurium in the presence of S9. Similarly, we observed a chromosomal damage in HepG2 cells with significant increases of micronuclei and nucleoplasmic bridges. These data indicate that SCAR 4 and 5 complexes did not show genotoxicity in our models while SCAR 6 was considered mutagenic. This study presented a comprehensive genotoxic evaluation of SCAR complexes were shown to be genotoxic in vitro. All in all, further studies are required to fully elucidate how the properties can affect human health.
Keywords: Cisplatin; Cytotoxicity; Mutagenicity; Ruthenium(II) complexes; Tuberculosis